THE RELATIONSHIP BETWEEN INTERNAL QUALITY ASSURANCE OF MALARIA PARASITE EXAMINATION WITH THE QUALITY OF MALARIA PREPARATIONS - Rita Permata Sari; Vetra Susanto; Fuji Verdian Putra; Endang Suriani; Yustitis Akbar; Meri Wulandari (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2023)
Internal Quality Assurance of malaria is a mandatory activity carried out by the malaria examination laboratory which includes a whole series of malaria examinations from pre-analytical, analytical, and post-analytical carried out with the aim of obtaining good malaria microscopic examination results in the form of good quality preparations. So far, there has not been much internal quality assurance associated with quality assessment. The purpose of this study was to determine the relationship between internal quality assurance and the assessment of the quality of malaria preparations in the laboratory of RSUD Umbu Rara Meha Waingapu. This type of research is an analytical quantitative approach with a cross sectional design The sample in this study is the total sample. Seven laboratory officers who carried out microscopic examination of malaria were interviewed and observed regarding the implementation of internal quality assurance from the pre-analytical to post-analytical stages, then 23 positive preparations were taken in 2021 and macroscopic and microscopic observations were carried out and an assessment of the quality of malaria preparations was carried out. Statistical analysis using the Pearson test processed using SPSS 25. The results of the study found that the percentage for the implementation of Internal Quality Assurance was 86%, while the percentage of preparate quality was 82%. Based on the Pearson correlation test between the two variables of internal quality assurance and also the quality of malaria preparate obtained a p-value of 0.010 where p < 0.05 which means there is a relationship between internal quality assurance and the quality of malaria preparate.